Membangun orientasi kewirausahaan dan lingkungan kerja untuk meningkatkan kinerja UKM - Sutrisno (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2023)
This study aims to develop the concept of entrepreneurial orientation and work environment in an effort to improve the performance of SMEs in the batik industry in Pekalongan city. This type of research is an explanatory study. This study tried to test hypotheses about the relationship between variables. The results of this study concluded that in the current friendly business environment, entrepreneurial orientation has an influence on the performance of SMEs in the batik industry in Pekalongan city, environmental conditions have a positive and significant influence, but the future business environment conditions cannot be predicted so it is necessary to anticipate several alternative problem solving that will occur. Therefore, it is necessary to run a business efficiently. The condition of the business environment can force companies to take advantage of entrepreneurial orientation to achieve business performance, but the company is not necessarily able to overcome this.